Co-application of fly ash and zeolite increases N uptake but decreases P uptake and biomass of rice fertilized with fermented liquid manure - Lee, Se-In; Ham, Jong-Hyun; Baek, Nuri; Kim, Han-Yong; Choi, Woo-Jung (Soil science and plant nutrition (Tokyo), 2025)
Fermented liquid pig manure (LPM) can be used as a nutrient source to replace synthetic fertilizers (SF). However, concerns remain regarding nitrogen (N) and phosphorus (P) losses from rice (Oryza sativa L.) paddies fertilized with LPM. Fly ash (FA) has a high calcium content (Ca) and zeolite (Z) has a high negative-charge; thus, they can immobilize P and N through the fixation of P with Ca and NH 4 + onto negatively charged sites, respectively. This study investigated the effects of the co-application of FA and Z (FAZ) on the nutrient availability and growth of rice fertilized with LPM. Four treatments were evaluated: no input (control), synthetic fertilizer (SF), and LPM at two levels, with or without FAZ application, for 104 days. The pH (pH water ), electrical conductivity (EC water ), N (N water ), and P (P water ) concentrations in the ponding water of rice fields were analyzed 18 times during rice growth. The rice biomass and uptake of N and P were measured, and the concentrations of mineral N and available P in soil were determined after harvest. LPM application increased (p < 0.001) N and P availability in the absence of FAZ, leading to rice biomass comparable to that of SF. However, FAZ diminished the fertilization effects of LPM on rice growth. The N water decreased by 50% and the rice uptake of N increased by 6% after FAZ application, probably because of the retention of N by Z and its subsequent release. By contrast, FAZ increased (p < 0.001) soluble P water (85% for LPM S ) and decreased (p = 0.004) P uptake (8%-40%), reducing the rice biomass by 20%-25%. The decreased P uptake is probably due to the strong immobilization of P by FA. Therefore, it is cautioned that P-limitation through immobilization of P by FA under alkaline conditions may hinder rice growth in FAZ-amended paddy fertilized with LPM. An appropriate application rate of FA for improved P nutrition needs to be explored.